Mobile Game-based Learning with GameMaker Studio - Ariesto Hadi (International Journal of Educational Technology and Artificial Intelligence, 2022)
In tapping the thriving mobile business, a study on mobile content development, specifically API, is urgently required. Highly wanted API is indeed for education, entertainment, and games that can be downloaded on Play Story. Thus, we develop a mobile game-based learning about multicultural learning. It was technically tested for its functionality, compliance, compatibility, and soaking. Furthermore, informal interviews and observations were conducted to assess potential players' insights. In addition, the multicultural game characters and the game plan developed for the game were tested for their appealing merit. Overall, responses were remarkably consistent. Participants overwhelmingly considered the game exciting and attractive, successfully delivering the intended learning content, easy to play, and simple to use. Findings also stressed two critical points (1) multicultural, appealing, and well-developed characters are essential elements to ensure a better learning experience, and (2) multicultural uniqueness must always be incorporated to ensure better learning motivation and increase mobile acceptance.